1997
DOI: 10.1093/oxfordjournals.aje.a009223
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Obesity, and Diabetes in Pregnancy

Abstract: Gestational diabetes mellitus (GDM) is the most common medical complication of pregnancy. Women with GDM are at elevated for numerous maternal health complications, and their infants are at elevated risk for death and morbidity. Management of GDM has traditionally been through diet and close monitoring of glucose levels, with initiation of insulin therapy when diet alone fails to maintain euglycemia. Recently, however, it has been suggested that alternative treatment modalities, such as exercise, may overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
116
4
13

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(144 citation statements)
references
References 10 publications
3
116
4
13
Order By: Relevance
“…It is possible that this association could be revealed to be significant using a more appropriate definition of physical activity. Exercise, in fact, seems associated with reduced rates of GDM particularly in obese women [9] in line with data of literature showing a protective effect of physical activity on the risk of Type II diabetes in women [38±39].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is possible that this association could be revealed to be significant using a more appropriate definition of physical activity. Exercise, in fact, seems associated with reduced rates of GDM particularly in obese women [9] in line with data of literature showing a protective effect of physical activity on the risk of Type II diabetes in women [38±39].…”
Section: Discussionsupporting
confidence: 88%
“…A lack of exercise seems to be an important risk factor for pregnant women who are obese only [9]. It has recently been shown that women with recurrent GDM had a higher overall intake of fat (as percentage of energy) than those without recurrences [10].…”
mentioning
confidence: 99%
“…This study found a non significant reduction of gestational diabetes mellitus risk for women who were vigorously physical active or did brisk walking before pregnancy. Dye et al 70 , also in 1997, found that inactive women presented OR: 1.9 (95%CI: 1.2-3.1) for gestational diabetes mellitus, compared to active women, only among those with BMI pre-pregnancy > 33. This study considered as physical activity those activities performed during leisure time.…”
Section: Physical Activitymentioning
confidence: 95%
“…Another example is obesity that has been a real threat to quality human life, which can be prevented at least in part via manipulating gestational characteristics of foetal cellular omics [4]. Regular, appropriate and adequately intensive physical activity during all phases of pregnancy can improve maternal intermediary metabolism by enhancing insulin sensitivity and minimizing gestational visceral adiposity and diabetes [1,[4][5][6][7]. This could basically enhance foetal genomic status in preventing obesity and dealing with glucose intolerance at certain unique times over the resulting individual lifespan.…”
Section: Discussion Of Philosophymentioning
confidence: 99%